Flow through various porosity of circle grid perforated plate with orifice plate flowmeter - Razali, Ahmad Hadi; Nordin, Normayati; Sapit, Azwan; Alias, Zainal Abidin (FAZ Publishing, 2020)
Most of the plant industry is required to measure the flow rate more accurately to meet plant operation and cost accounting objectives. The opposing concern of improving flow meter accuracy is resolved by using flow conditioners. The distance of implementation of flow conditioner upstream of the orifice plate flowmeter also needs to be addressed. The purpose of this study is to analysis the porosity of the circle grid perforated flow conditioner towards orifice plate flowmeter’s accuracy and to determine the ideal distance of flow conditioner upstream of the orifice plate flowmeter. In this investigation, a variety of designs of the flow conditioners based on a porosity were installed with different distance upstream of the orifice plate in conjunction with the different disturbances to assess the effects of these devices on the measurement of the mass flow rate. Experimental investigation depends on three patterns of the perforated plate in a variety of diameter ratio or porosity which is β equals to 0.38 for the first plate, 0.5 for the second plate and 0.7 for the final plate. These fractal patterns will then react to five openings of speed controller of the centrifugal inline fan. Data gains for all three plates showed that there is an increment of pressure drop and change in discharge coefficient of the orifice with lower β value of fractal flow conditioner. This investigation also compares the various distance of flow conditioner upstream of the orifice plate flowmeter, thus proved that shorter pipe length produced higher pressure drop.